Environmental Impacts of Contrasted Groundwater Pumping Systems Assessed by Life Cycle Assessment Methodology: Contribution to the Water–Energy Nexus Study†. (17th December 2014) - Pradeleix, Ludivine; Roux, Philippe; Bouarfa, Sami; Jaouani, Bochra; Lili‐Chabaane, Zohra; Bellon‐Maurel, Veronique
Abstract Most studies on the environmental performance of irrigation have focused on the water–food–energy nexus, i.e. relationships between food production, water consumption and energy. However, water and energy are not the only relevant indicators of the environmental performance of irrigation systems. Life cycle assessment (LCA) is a holistic method that is well suited to comprehensive assessment. This paper aims at using LCA to assess the environmental impacts of contrasted groundwater pumping systems in semi‐arid central Tunisia. In line with previous studies, our results confirm that for groundwater pumping, energy has the highest environmental impacts on human health, the ecosystem and resource depletion. Our work also highlights that along with pump efficiency, the type of power source must be considered when ranking pumping systems based on environmental performance. Indeed, diesel‐powered pumping systems are more harmful than electric pumps when electricity is generated from natural gas and diesel‐powered pump efficiency is low. However, the diesel pumping system becomes the best option when electricity is derived from coal and diesel‐powered pump efficiency exceeds 12%. Finally, water depletion has been shown of great importance in this study, and ongoing LCA improvements should facilitate a more comprehensive picture of these site‐specific impacts. Copyright © 2014 John Wiley & Sons, Ltd.